TINGKAT KINERJA KONSELOR PROFESIONAL - Abdul Murad (Universitas Negeri Malang, 2012)
Abstract: The Performance Level of Professional Counselors. The study was aimed at describing the performance level of professional counselors with regard to educational background and school climate. Analytic-descriptive method was applied in the study. The sample of the study consisted of 64 state senior high school counselors in Bandung, Malang, and Padang. The data were collected using a questionnaire, which were finally analyzed descriptively. The results of this study indicated that the counselors who had the counseling education background were at a high level of performance and those who did not have the counseling education background were at the medium level of performance. Those who worked in the supportive school climate were at high level of performance and those who worked in the less supportive school climate were at the medium level of performance. Abstrak: Tingkat Kinerja Konselor Profesional. Penelitian ini bertujuan untuk mendeskripsikan tingkat kinerja konselor profesional ditelaah dari latar belakang pendidikan dan iklim sekolah. Penelitian ini menggunakan metode deskriptif analitik. Sampel penelitian terdiri dari 64 konselor SMAN di kota Bandung, Malang, dan Padang. Data dikumpulkan menggunakan kuesioner, yang akhirnya dianalisis secara deskriptif. Hasil-hasil penelitian menunjukkan bahwa tingkat kinerja konselor yang berlatar belakang pendidikan konseling berada pada kategori tinggi. Sebaliknya, tingkat kinerja konselor yang bukan berlatar belakang pendidikan konseling berada pada kategori sedang. Tingkat kinerja konselor yang bertugas dalam iklim sekolah yang suportif berada pada kategori tinggi dan tingkat kinerja konselor yang bertugas dalam iklim sekolah yang kurang suportif berada pada kategori sedang.